2021
DOI: 10.1126/sciadv.aba9958
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress reduces pocilloporid coral resilience to ocean acidification by impairing control over calcifying fluid chemistry

Abstract: The combination of thermal stress and ocean acidification (OA) can more negatively affect coral calcification than an individual stressors, but the mechanism behind this interaction is unknown. We used two independent methods (microelectrode and boron geochemistry) to measure calcifying fluid pH (pHcf) and carbonate chemistry of the corals Pocillopora damicornis and Stylophora pistillata grown under various temperature and pCO2 conditions. Although these approaches demonstrate that they record pHcf over differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 84 publications
8
58
2
Order By: Relevance
“…In addition, photosynthetic products have been suggested to be used as precursors for skeletal organic matrix biosynthesis [39]. An increased translocation of photosynthates from S. microadriaticum would thus considerably support the enhanced synthesis of organic matrix in the corals, and it would overall increase the host ability to cope with the effects of OA [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, photosynthetic products have been suggested to be used as precursors for skeletal organic matrix biosynthesis [39]. An increased translocation of photosynthates from S. microadriaticum would thus considerably support the enhanced synthesis of organic matrix in the corals, and it would overall increase the host ability to cope with the effects of OA [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if pH i in corals is regulated more tightly than extracellular body fluids (pH e ) during stress, as it is in other marine invertebrates (Tresguerres et al, 2020), the interactive effects of temperature stress and hypercapnia on pH i and pH e regulation may be particularly detrimental for biomineralization, which occurs in extracellular pockets of fluid located between the coral epidermis and the skeleton. Indeed, recent work has found that heat stress impairs coral regulation of calcifying fluid pH e with concurrent declines in calcification (Guillermic et al, 2021;Schoepf et al, 2021), which raises the question of whether coral pH i maintenance may be occurring at the expense of pH e during stress. Because the dynamics and mechanisms of acid-base regulation differ greatly between species and cell types (Tresguerres et al, 2017(Tresguerres et al, , 2020, it is critical that future work describes the molecular mechanisms that dictate these organismal responses to climate change stressors in order to better predict their ability to acclimatize and adapt to the ongoing climate crisis.…”
Section: Heat Stress Differentially Alters Intracellular Ph and Impairs Cellular Acidification Resilience In Bleaching-resistant And Bleamentioning
confidence: 99%
“…The potential effects of heat stress on acid–base regulation pose a particular challenge for maintaining coral calcification, as biomineralization is highly pH‐dependent (Barott et al, 2020; McCulloch et al, 2012; Venn et al, 2011, 2012). Indeed, recent studies have found that temperature stress alters the pH of the external calcifying fluid and depresses calcification (Guillermic et al, 2021; Schoepf et al, 2021), highlighting the need to better understand the physiology of coral climate change responses across biological scales.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the nuances of how coral reef calcifiers can adapt to global change, such as ocean acidification, we need to better understand the ionic composition at the site of calcification. Unfortunately, in the short-term tropical calcifying organisms show little acclimatization potential to ocean acidification [101] particularly when coupled with thermal stress [102], but there are few examples of resistance by altering the ionic concentrations in the ECF, for example Ca [43]. Additionally, this study considered the influence of various Ca:CO 3 stoichiometry and Mg concentrations on the precipitation rates and morphology of CaCO 3 in a homeostatic experiment.…”
Section: Discussionmentioning
confidence: 99%